2006
DOI: 10.1007/s00199-006-0111-9
|View full text |Cite
|
Sign up to set email alerts
|

Unobservable Contracts as Precommitments

Abstract: Strategic delegation, Unobservable contracts, C72, D80, L13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…This is an example illustrating the main results in Koçkesen and Ok (2004) and Koçkesen (2007) which state that all Nash equilibrium outcomes can be supported with unobservable (but complete and non-renegotiable) contracts.…”
Section: Ultimatum Bargainingmentioning
confidence: 79%
See 2 more Smart Citations
“…This is an example illustrating the main results in Koçkesen and Ok (2004) and Koçkesen (2007) which state that all Nash equilibrium outcomes can be supported with unobservable (but complete and non-renegotiable) contracts.…”
Section: Ultimatum Bargainingmentioning
confidence: 79%
“…Koçkesen and Ok (2004) and Koçkesen (2007) addressed the same question within the context of extensive form games and showed that all (and only) Nash equilibrium outcomes of the original game can be supported as a sequential equilibrium outcome of the delegation game. In particular, they showed that outcomes that are not subgame perfect in the original game may arise as a sequential equilibrium outcome of the induced delegation game, i.e., unobservable contracts may have a strategic effect as long as they are non-renegotiable.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this case, condition (2) would have the individually rational payoff defined as b 2 ). In that case, the result would be the exact analog of those in models without asymmetric information, i.e., Koçkesen and Ok (2004) and Koçkesen (2007).…”
Section: ) Of the Original Game G Can Be Supported With Unobservable mentioning
confidence: 99%
“…The effects of unobservable and non-renegotiable third-party contracts are also well-understood: Nash equilibrium outcomes of a game with and without third-party contracts are identical (Katz (1991)). In fact, all (and only) Nash equilibrium outcomes of the original game can be supported as a sequential equilibrium outcome of the game with unobservable and non-renegotiable contracts (Koçkesen and Ok (2004) and Koçkesen (2007)). 3 The strategic role of renegotiable contracts is less understood and the pioneering contribution is provided by Dewatripont (1988 Dewatripont (1988), is that by allowing secret renegotiation, Caillaud et al (1995) enhanced the realism of the model and clarified the role of strategic contracting.…”
Section: Relationship To the Literaturementioning
confidence: 99%